Rootless survivors in plants - Kondhare, Kirtikumar R.; Lavhale, Santosh G.; Giri, Ashok P. (Plant Science, 2026)
The root system provides anchorage, uptakes of nutrients and water, and forms different associations within soil environments that govern plant fitness, crop performance, and yield. Auxin controls almost all aspects of root development. Both shoot- and root-derived auxins contribute to formation of polar auxin transport, which is crucial for establishing and maintaining normal root architecture. The coordinated activities of auxin influx and efflux carriers establish necessary polar auxin transport. A variety of natural metabolites and synthetic compounds are shown to interfere with auxin metabolism, transporters and signaling pathways having a negative impact on root growth. In this review, we highlight the reports demonstrating the observance of rootless phenotypes in plants and associated molecular mechanisms. Rootless phenotypes can be produced under in vitro culture conditions by modulation of phytohormone combinations (especially auxin and cytokinin), and supplementation of naturally-occurring flavonoids and their glycosides or synthetic auxin transport inhibitors (1-Nnaphthylphthalamic acid and 2,3,5-triiodobenzoic acid) or under in vivo conditions by modulation of several genes directly or indirectly associated with auxin biology. Further, we describe the crosstalk of naturallyoccurring flavonoids (e.g. kaempferol, quercetin), their glycosides, and other metabolites (e.g. azelaic acid, cis-cinnamic acid) with auxin transporters, their mobile nature, and influence on root development. Moreover, we provide evolutionary perspective on the auxin and flavonoid pathways and their possible roles in naturally rootless plants. We also emphasize the importance of rootless or reduced root growth phenotypes in modern agriculture, and the pressing needs to utilize naturally occurring auxin transport inhibitors for industrial and research applications.
Keywords: Auxin; Flavonoid; Flavonoid-glycoside; Polar auxin transport; rootless